Correct Typing Dapat Meningkatkan Efisiensi Kerja Pengguna dalam Dunia Pendidikan dan Profesional - Anisa Maharani; Diva Cherylla Tarmidi; Kayla Putri Eriani; Rofi Ahmad Najib Ululabsor (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2025)
This study aims to analyze the impact of the Correct Typing feature in Google Workspace on user work efficiency in educational and professional contexts.Using a descriptive quantitative approach and purposive sampling technique, data were collected through electronic questionnaires that evaluated users' perceptions of various aspects of the feature's usage.The research results show that the Correct Typing feature is very well received by users because it can increase typing speed, reduce errors, and expedite the document completion process.Most respondents felt satisfied and intended to continue using this feature sustainably.These findings emphasize the importance of integrating the Correct Typing feature in efforts to enhance productivity, as well as the need for developing specialized training to optimize its use to the fullest.